2017
DOI: 10.1016/j.ijggc.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

An operational approach for the designing of an energy integrated oxy-fuel CFB power plant

Abstract: Oxy-fuel combustion is one of the key alternatives for coal power production with near-zero CO 2 emissions. Technology has been successfully proved in demonstration facilities and the next step is to improve its efficiency to facilitate the application to future commercial installations. The use of pure oxygen reduces the total volume of flue gases and concentrates CO 2 at boiler outlet. Nevertheless, there is an important energy penalty and efficiency of the power plant substantially decreases around 10-12 ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Main challenges for the development of oxy-fuel combustion plants are related to the reduction of the large energy penalties caused by ASU and CPU stages (air separation unit and compression and processing unit, respectively), with a target of 7-9 % [7]. Besides energy integration and optimization, other solutions can also contribute to increase the efficiency and operating manageability of these plants.…”
mentioning
confidence: 99%
“…Main challenges for the development of oxy-fuel combustion plants are related to the reduction of the large energy penalties caused by ASU and CPU stages (air separation unit and compression and processing unit, respectively), with a target of 7-9 % [7]. Besides energy integration and optimization, other solutions can also contribute to increase the efficiency and operating manageability of these plants.…”
mentioning
confidence: 99%
“…In most literature, the typical CO 2 pressure and temperature ranges are 8–20 MPa and 0–50 °C, respectively, ,, and the compression ratio is usually in the range of 1.6–2.4. ,, In this work, CO 2 is compressed to 15 MPa and is ready for delivery and storage. The compression process includes six stages, as shown in Figure .…”
Section: Process Model Developmentmentioning
confidence: 99%
“…Kotowicz et al showed that the efficiency penalty was reduced to 7.3% after heat recovery from an ASU and the exhaust flue gas. Espatolero et al recovered the heat from an ASU and a flue gas compression and purification unit (CPU), and the net electric efficiency was increased by approximately 3% without operational restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Рассмотрены проблемы развития систем теплоснабжения [10], где одним из вариантов для создания автономных систем отопления является использование электрического тока. Имеются также ряд зарубежных публикаций, направленных на создание новых источников тепла и повышение эффективности работы систем отопления [11][12][13]. Исследования основаны на использовании известных методов и законов теории теплообмена [14,15].…”
Section: Introductionunclassified